Restorasi pendidikan Indonesia : menuju masyarakat terdidik berbasis budaya - Universitas Negeri Yogyakarta. Lembaga Kajian Mahasiswa (Sleman, Jogjakarta : Ar-Ruzz Media, 2011)
On the restoration of national education system in Indonesia; collection of articles.
Includes bibliographical references (p. 175-184) and index.